A Comparison of the Impact of Two Social Prescribing Patient Navigation Models on Health Care Utilization - Mahbub, Adiba (Université d'Ottawa | University of Ottawa, 2024)
Objectives: This study compared the effects of two lay patient navigation models (ARC in-person primary care-based navigation vs. Ontario-211 provincially funded remote navigation) within a social prescribing program on health care utilization in Ontario. Methods: We conducted comparative analyses of patients who participated in the larger-scale ARC-211 RCT, using study data linked to health administrative data housed at ICES. Changes in outpatient care use between pre and post intervention periods and post-intervention acute care use were compared between study arms. Results: There was a trend towards a greater decrease in number of outpatient visits in the post-intervention period in the ARC arm compared to the 211 arm, and a trend of greater odds of at least one acute care episode in the 211 arm. These results were not statistically significant. Conclusions: The ARC in-person patient navigation approach may be beneficial in reducing health care utilization and warrants further investigation.
Keywords: epidemiology; social prescribing; health care utilization